STIMULATION INTELLECTUAL AND INDIVIDUALIZED CONSIDERATION IN LEADING EMPLOYEES: A STUDY IN ONE LOCAL AUTHORITY - Azman Ismail; Shairazi Samsudin; Asmai Ishak (Jurnal Siasat Bisnis, 2008)
This study was conducted to measure the effect of transformation leadership character¬istics (i.e., intellectual stimulation and individualized consideration) and empowerment on service quality using 110 usable questionnaires gathered from employees who have worked in one city based local authority in Sarawak, Malaysia (AUTHORKEM). Stepwise regression analysis showed that the inclusion of empowerment in the analysis had increased the effect of transformational leadership characteristics on service quality. The result confirms that em¬powerment does act as a full mediating role in leadership model of the studied organization. Key words: transformational leadership, empowerment, service quality